Cold war democracy : the United States and Japan - Miller, Jennifer M. (Harvard University Press, 2019)
Jennifer M. Miller examines the evolution of ideas about democracy during the Cold War by charting the development of the alliance between the United States and Japan from the postwar occupation into the 1960s. She argues that both countries were deeply concerned with sustaining a commitment to the idea of democracy in the aftermath of World War II. This allegiance to democracy as a rhetorical and ideological platform created new opportunities and constrained the choices of actors in each country and greatly influenced each country's policies regionally and globally. She shows that a "clash of visions" both inside Japan and the US and between diplomats and leaders on both sides of the alliance helped to sustain the commitment to democracy, rather than tearing it free. But, in doing so, many of the opportunities that democracy promised--both domestically and internationally--were lost.--